2015
DOI: 10.4025/actascibiolsci.v37i3.27853
|View full text |Cite
|
Sign up to set email alerts
|

<b>Space-time variation in the composition, richness and abundance of social wasps (Hymenoptera: Vespidae: Polistinae) in a forest-agriculture mosaic in Rio Grande do Sul, Brazil

Abstract: Wasps, important agents for the control of insect population, have been scantily studied in the Brazilian State of Rio Grande do Sul. Current study investigates monthly variations of social wasps in microhabitats within a forest-agriculture mosaic. Samples were collected between February 2013 and February 2014, through active search and baited traps made from 2 L transparent PET bottles, in five microhabitats, namely, forest, monoculture, polyculture and the edges between the forest fragment and monoculture an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
3
3
3
Order By: Relevance
“…Thus, bait traps were more efficient for collecting wasps of the Epiponini. This result is contrasting to other ones reporting the active search as the most efficient method for Epiponini in comparison to bait traps (Souza & Prezoto 2006;Klein et al 2015). However, these works also resulted in the active search being the most effective to sample species richness of other tribes, as resulted in the present work.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, bait traps were more efficient for collecting wasps of the Epiponini. This result is contrasting to other ones reporting the active search as the most efficient method for Epiponini in comparison to bait traps (Souza & Prezoto 2006;Klein et al 2015). However, these works also resulted in the active search being the most effective to sample species richness of other tribes, as resulted in the present work.…”
Section: Resultscontrasting
confidence: 99%
“…The work of Klein et al (2015), carried out in deciduous forests of the State of Rio Grande do Sul, also reported a low species richness and abundance collected by bait traps when compared to more open environments, which are scarcer in resources, such as monoculture borders close to forests. Therefore, it is suggested that for these environments, other sampling methods should be used, such as Malaise trap (Somavilla et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The high abundance of Agelaia and Polybia registered in the current and other studies indicates that species of these genera find it easy to colonize several different types of microhabitats due to their protected nests, method of foundation and great number of individuals, which gives their colonies greater chances of success (Hermes & Köhler, 2004). In this study, their abundance was higher in adjacent forest and interior of the crop, showing a great capacity for dispersion, unlike the results of others studies where usually the uniform environments and interior of the crops lower their abundance, and suggests that these species encounter barriers to use resources outside the better-conserved environments (Klein et al, 2015).…”
Section: Resultscontrasting
confidence: 99%
“…their colonies greater chances of success (Hermes & Köhler, 2004). In this study, their abundance was higher in the interior of the tobacco crop, showing a great capacity for dispersion, unlike the results of others studies where usually the uniform environments and interior of the crops lower their abundance, and suggests that these species encounter barriers to use resources outside the better-conserved environments (Klein et al, 2015). Interestingly, the six most abundant species of this study, namely Agelaia multipicta, A. vicina, Brachygastra lecheguana, Polybia ignobilis, P. scutellaris, and P. sericea, are species with wide distribution in Rio Grande do Sul, being registered in several localities in the state (Somavilla et al, 2011), in this way, the great abundance in this study, together with the wide distribution and habit of predation, can be considered species with potential in the biological control of tobacco, especially caterpillars of Lepidoptera, the most important pests in the culture.…”
Section: Discussioncontrasting
confidence: 99%